2010
DOI: 10.1007/s00425-010-1134-9
|View full text |Cite
|
Sign up to set email alerts
|

Boron toxicity is alleviated by hydrogen sulfide in cucumber (Cucumis sativus L.) seedlings

Abstract: Boron (B) is an essential micronutrient for plants, which when occurs in excess in the growth medium, becomes toxic to plants. Rapid inhibition of root elongation is one of the most distinct symptoms of B toxicity. Hydrogen sulfide (H(2)S) is emerging as a potential messenger molecule involved in modulation of physiological processes in plants. In the present study, we investigated the role of H(2)S in B toxicity in cucumber (Cucumis sativus) seedlings. Root elongation was significantly inhibited by exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(86 citation statements)
references
References 46 publications
7
78
0
Order By: Relevance
“…Recent studies in plants revealed that H 2 S plays multiple roles in the modulation of various physiological processes [3], such as copper, cadmium, drought, salinity and heat et al [6][7][8][9][10]. In addition, our results indicate that the content of H 2 S was rapidly increased by low temperature.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recent studies in plants revealed that H 2 S plays multiple roles in the modulation of various physiological processes [3], such as copper, cadmium, drought, salinity and heat et al [6][7][8][9][10]. In addition, our results indicate that the content of H 2 S was rapidly increased by low temperature.…”
Section: Discussionsupporting
confidence: 57%
“…Many data indicate that most of the endogenously synthesized H 2 S occurred via L-cysteine desulfhydrase (LCD, EC4.4.1.1) and D-cysteine desulfhydrase (DCD, EC4.4.1.15) in high plants [2][3][4][5]. Recent studies show that H 2 S is involved not only in plant responses to drought and copper stresses but also in tolerance to salinity, heat, cadmium, boron and chromium stresses [6][7][8][9][10]. It is reported that exogenous H 2 S can enhance the resistance of plants to drought stress [11][12][13][14] and copper stress [15,16] by improving the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD).…”
Section: Introductionmentioning
confidence: 99%
“…In cucumber (Cucumis sativus) seedlings, root elongation was significantly inhibited by exposure of cucumber seedlings to solutions containing 5 mM boron (B), but this inhibitory effect was substantially alleviated by treatment with NaHS, a hydrogen sulfide donor (Wang et al 2010). In addition, under chromium (Cr) stress, the percentage of germination of wheat seeds decreased, but this decrease could be alleviated by pretreatment with NaHS in a dose-dependent manner (Zhang et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, numerous studies have shown that sulfide increases tolerance/resistance against stress conditions, such as metal stress (Zhang et al 2008 ;Dawood et al 2012 ;Wang et al 2010 ;Sun et al 2013 ;, drought (Jin et al 2011 ), hypoxia (Cheng et al 2013 ), salinity (Christou et al 2013 ;Wang et al 2012 ), and heat . Moreover, sulfide has been also demonstrated to regulate many essential plant processes, like photosynthesis (Chen et al 2011 ), stomatal movement (Garcia-Mata and Lamattina 2010 ;Lisjak et al 2010 ), flower senescence (Zhang et al 2011 ), and postharvest life of fruits (Hu et al 2012 ).…”
Section: Cysteine Homeostasis In the Cytosolmentioning
confidence: 99%